Logic in the Husserlian Context - Tito, Johanna Maria (My University, 1987)
The theme of logic runs through all of Husserl's writings, from his earliest Philosophy of Arithmetic, to his final Experience and Judgment. Husserl has even characterized phenomenology as a transcendental logic. I examine Husserl's notion of logic, and it turns out to be an interesting vehicle for bringing together two diverse aspects of Husserl's phenomenology. Which by many critics are thought to be incompatible with each other, namely the purely formal aspect of phenomenology, and the aspect of phenomenology when deals with life. I show how Husserl develops a transcendental logic by going through the tradition of formal logic. He argues that traditional formal logic is not a pure logic, but is one which presupposes the world. Husserl goes beyond this and develops a logic which is pure, one based on the pure transcendental ego in which no world is presupposed. This introduces a "subjective" factor into logic. I show that no logical psychologism is implied. At the same time I show that this pure ego is the centre of life, and that it can do justice to the speculative demands contained in the concept of life. This is done in three ways: by demonstrating that i) the notion of pure transcendental ego is compatible with and can do justice to the life related concepts contained in Freudian psychology, ii) the notion of pure transcendental ego can account of other selves, Also a notion found in the concept of life, and iii) Husserl's essentialist approach is compatible with a teleological-historical approach, the latter introducing a factual element. Finally I show that Husserl's transcendental logic, with its notion of the constituting subject, is compatible with the logic of Frege.
Keywords: Husserlian; Logic